Wisata Edukasi Arak Bali di Kabupaten Karangasem - Adelia Shindy Bella, Putu; Kastawan, I Wayan; Made Suartika, Gusti Ayu (Jurnal Arsitektur Universitas Udayana; Vol 10 No 01 (2022): Jurnal Arsitektur, Universitas Udayana, 2022)
The Educational Tourism of Arak Bali is an education and tourism facilities located in Karangasem Regency. The Educational Tourism of arak Bali has three functions that divided into several facilities. Each facility spread over several buildings, so it is necessary to choose the circulation elements according to the designated concepts. The circulation element consists of approach, entrance, configuration of the path, path-space relationships, and form of the circulation space. The purpose of this research is to analyze how the design of Educational Tourism of Arak Bali implement the circulation elements on site and building mass. This research used descriptive analysis method equipped with design visualization scheme. The results of this research is the design of Educational Tourism of Arak Bali applies all sirculation elements so that it can support and integrate activities on site and building mass effectively.